Quantitative analysis of exosomes in the aqueous humor of Korean patients with pseudoexfoliation glaucoma - An, Hyo Jung; Cho, Hyun-kyung; Song, Dae Hyun; Kee, Changwon (Scientific reports, 2022)
We aimed to quantitatively analyze the exosome and its cargo in individual aqueous humor (AH) samples from pseudoexfoliation (PEX) glaucoma patients compared to controls using a novel detection platform. We investigated the size distribution and measured the quantitative exosome particle counts in each AH sample. AH (80–120 µL) was obtained during cataract surgery or glaucoma filtering surgery from 12 Korean subjects (six with PEX glaucoma and six age-matched controls). The mean size of the exosomes was 58.9 ± 18.5 nm measured by a tangential flow filtration system using single-particle interferometric reflectance imaging sensor. Exosome particle count in each CD 63, CD 81, and CD9 spot was significantly greater in PEX glaucoma than in controls in total, CD 63, CD9, syntenin, and scattering(all p < 0.003). The CD63 spot showed a particle count of 8319.1 ± 797.7 in PEX glaucoma patients and 4786.8 ± 1302.1 in controls ( p = 1.88E−11). Individual fluorescent capture spot images also revealed denser exosome particles in PEX patients than in controls. Syntenin, indicating exosomal origin, was detected in all AH samples. Exosomes differentially detected in AH suggest the possible role of exosomes in the pathogenesis of PEX glaucoma.